THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN HISTORY EDUCATION AT SMA NEGERI 1 BATUDAA PANTAI - Malela, Hesti; Mohamad, Sutrino; Manay, Helman (Satmata: Journal of Historical Education Studies, 2025)
This study aims to explore history teachers’ perspectives on the Merdeka Belajar (Independent Learning) policy, the implementation of history instruction under the Merdeka Curriculum, and the challenges encountered by both teachers and students during its application. The research focuses on a case study of SMA Negeri 1 Batudaa Pantai, a pioneering school in implementing the Merdeka Curriculum for the History subject. Employing a qualitative approach with a case study design, data were collected through interviews and observations involving the Principal, Vice Principal, History teacher, and students, complemented by supporting documents. The data were analyzed using the stages of data reduction, categorization, and synthesis to identify patterns and connections. The novelty of this research lies in its in-depth investigation at a non-pilot school, specifically highlighting issues such as limited learning resources, poor internet access, and initial teacher adjustment without sufficient training. Findings reveal that although the curriculum has been implemented since 2022, significant adaptation challenges persist. Initial teacher responses tended to be critical, especially concerning the complexity of lesson planning. Nevertheless, the implementation has followed the curriculum framework, utilizing various learning media, including the internet. The main constraints faced include limited instructional time and inadequate learning facilities.